(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
The research results and the results obtained allow us to draw the following conclusions about the preparation for professional activities of students of professional colleges through interdisciplinary relationships. The fundamental and theoretical, as well as the feasibility of special organizational preparation of college students for the introduction of inter subject communications using information technology in the development of modern integrative thinking is fundamental. Analysis of the implementation of the state of inter subject communications in didactics from the point of view of the unity of the material world. An important methodological principle for the implementation of inter subject communications is the differentiation and synthesis of new knowledge.